Perspectives of Homeowners on Sustainability and the Design of Energy-Efficient Residential Architecture (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The paper presents an investigation into the householder perception of low-energy dwellings. Iraq has an infamous reputation of being a country with an abnormal consumption and emission of carbon dioxide. Therefore, an online survey (398 respondents) was conducted across Iraq to determine their opinion on the knowledge and awareness of sustainability and low energy dwellings. It considers the manners and the characteristics of the current dwellers in terms of energy usage and their understanding of what constitutes sustainable and low-energy dwellings. The results highlight how a lack of householder's knowledge and awareness of low-emission and sustainable energy sources and entrance restrictions have restricted the conversion of current residential stock to contemporary environmentally friendly dwellings.